PERKEMBANGAN STRUKTUR AERENKIM RHIZOFOR - Enny Susiyawati, ; Johanes Djoko Budiono, ; Rinie Pratiwi Puspitawati, (Matematika dan Sains, 2010)
Rhizophora mucronata is one of part of mangrove which adapt to environment by forming aerenkim, especially at its rhizophore. Aerenkim of rhizofore submerged in substrat developed faster than that one on substrat. Therefore research about aerenkim structure development was very important to be conducted. This research was obseravational research. Observation was done on rhizophore preparate made by parafin method and coloring using safranin. Results of research showed that during develpoment period, aerenkim of rhizophore R. mucronata experience structure developmet. Aerenkim of rhizophore submerged in substrat developed faster than that one on substrat (air root). Aerenkim of R. mucronata was formed through sizogen way. is one of part of mangrove which adapt to environment by forming aerenkim, especially at its rhizophore. Aerenkim of rhizofore submerged in substrat developed faster than that one on substrat. Therefore research about aerenkim structure development was very important to be conducted. This research was obseravational research. Observation was done on rhizophore preparate made by parafin method and coloring using safranin. Results of research showed that during develpoment period, aerenkim of rhizophore R. mucronata experience structure developmet. Aerenkim of rhizophore submerged in substrat developed faster than that one on substrat (air root). Aerenkim of R. mucronata was formed through sizogen way.